2009
DOI: 10.1021/jp903788n
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Brønsted Acid Strength and Local Structure in Zeolites

Abstract: As an index of acid strength, ammonia adsorption energies (E ads ) were calculated with density functional theory on cluster models of Brønsted acid sites belonging to FAU, BEA, MFI, FER, MWW, and MOR structures, which were selected because of the availability of experimental data and industrial importance.The calculated E ads were reasonably consistent with experimental results from the ammonia IRMS-TPD (infrared mass spectroscopy-temperature-programmed desorption) method. The calculated value was slightly (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
115
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 60 publications
7
115
0
Order By: Relevance
“…In such a case, the Al and H positions are selected based on preliminary energy calculations and/or spectroscopic researches, as we have shown in other types of zeolites [17][18][19]. However, the Al sitting in the TNU-9 zeolite has not been studied, and therefore, the selection for these calculations had to be carried out purely on assumptions.…”
Section: Dft Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a case, the Al and H positions are selected based on preliminary energy calculations and/or spectroscopic researches, as we have shown in other types of zeolites [17][18][19]. However, the Al sitting in the TNU-9 zeolite has not been studied, and therefore, the selection for these calculations had to be carried out purely on assumptions.…”
Section: Dft Calculationmentioning
confidence: 99%
“…The calculated and observed values are in reasonable agreement, supporting the validity of the IRMS-TPD technique. Moreover, it is pointed out that the microstructure around the acid site controls the acidic property, because the acid strength is thus varied by changing the structure of cluster models [19].…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Figure 9 shows the dependence of E des on AlO distance. Again, the open symbols show the data points in MOR, MWW, MFI, FER, BEA and FAU [18]; from this figure, the acid site models in very small spaces which caused steric hindrance for NH 4 ? cation has been excluded.…”
Section: Dft Calculationmentioning
confidence: 98%
“…Local geometry is believed to control the acid strength through bond angles and lengths around the AlOHSi unit. We have recently found that the AlO distance in the AlOHSi unit predominantly controls the charge of Brønsted OH group, presumably because Al center with Lewis acidity withdraws the electron of O in SiOH [18]. As a result, Brønsted acid strength (ammonia desorption energy) of the OH showed an inverse relation with the AlO distance.…”
Section: Dft Calculationmentioning
confidence: 99%
See 1 more Smart Citation